Strategi Pemasaran Desa Ubud sebagai Destinasi MICE - IGPB Sasrawan Mananda; Luh Gede Leli Kusuma Dewi (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
The concept of mass tourism has two seasons namely high season and low season to determine the number of tourist visits each year. Therefore the tourism industry tries to conduct a vigorous promotion by carrying out activities that can bring tourists to stay in one tourist destination. One of the activities that entrepreneurs do in the low season is to conduct activities called MICE (Meetings, Incentives, Conventions, and Exhibitions). This research uses qualitative analysis technique by applying the participatory principle involving MICE stakeholders, destination manager, travel agent managers, and tourists. Ubud Village as a tourist destination which has potential for MICE activities has not had a convention bureau. This is due to the characteristics of the tourists who come to Ubud and the needs required by the tourism industry managers which are different from other tourist destinations in Bali such as Badung regency and Denpasar municipality. During this time, the implementation of activities of MICE is dominated by incentives tourism activities (56.57%), exhibitions (31.72%), and meetings (11.71%). The SWOT results concluded that Ubud Village is still S > W and O ≥ T thus requiring an internal consolidation, but seeing O ≥ T, has potential for further development. Development strategy were using grand strategy which make the results such as growth, dominance, and maximum investment.